Reprenstasi Ketakutan Meninggalkan Kebudayan Batak Dalam Film Ngeri-Ngeri Sedap - Oktavia Permatasari Sihombing (STIKes Ibnu Sina Ajibarang, 2024)
This research explores the representation of fear in the context of leaving Batak culture as depicted in the film